Co‐infection by classic MYXV and ha‐MYXV in Iberian hare (Lepus granatensis) and European wild rabbit (Oryctolagus cuniculus algirus). Issue 4 (9th April 2022) - Abade dos Santos, Fábio A.; Dalton, Kevin P.; Carvalho, Carina L.; Casero, María; Álvarez, Ángel L.; Parra, F.; Duarte, Margarida D.
Abstract: Myxomatosis is an emergent disease in the Iberian hare ( Lepus granatensis ). In this species, the disease is caused by a natural recombinant virus (ha‐myxoma virus [MYXV]) identified for the first time in 2018 and has since been responsible for a large number of outbreaks in Spain and Portugal. The ha‐MYXV, which harbours a 2.8 Kb insert‐disrupting gene M009L, can also infect and cause disease in wild and domestic rabbits, despite being less frequently identified in rabbits. During the laboratory investigations of wild leporids found dead in Portugal carried out within the scope of a Nacional Surveillance Plan (Dispatch 4757/17, MAFDR), co‐infection events by classic (MYXV) and naturally recombinant (ha‐MYXV) strains were detected in both one Iberian hare and one European wild rabbit ( Oryctolagus cuniculus algirus ). These two cases were initially detected by a multiplex qPCR detection of MYXV and ha‐MYXV and subsequently confirmed by conventional PCR and sequencing of the M009L gene, which contains an ha‐MYXV‐specific insertion. To our knowledge, this is the first documented report of co‐infection by classic MYXV and ha‐MYXV strains either in Iberian hare or in European wild rabbit. It is also the first report of infection of an Iberian hare by a classic MYXV strain. These findings highlight the continuous evolution of the MYXV and the frequent host range changes that justify the nonstop monitoring of the sanitary condition of wild Leporidae populations in the Iberian Peninsula.